THE EFFECT OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE OFFICE OF TOURISM AND CULTURE OF SIMALUNGUN REGENCY - Irenes Tesya Sinaga; Demsi Aningsah; Jopinus R. Saragih (Universitas Efarina, 2020)
Department of Tourism and Culture Regency Simalungun is one _ service in ranks government Regency Simalungun . On research This For see influence environment work and motivation to performance employee at the Department of Tourism and Culture Regency Simalungun. The theory used in study This is theory Management source Power related humans _ with environment work , motivation and performance.Type study This is descriptive quantitative and properties study This is study explanation . Sample in study This as many as 30 people. Method data collection is carried out with interviews , distribution of questionnaires and studies documentation . The results of research on the hypothesis First show that environment Work No have positive influence _ However motivation influential positive to performance employee at the Department of Tourism and Culture Regency Simalungun . With equality regression as following : Y = 10.863 - 0.085 X1 + 0.187 X2